Religious culture management at SMP IT Tulang Bawang District - Suryono, Suryono; Pahrudin, Agus; Syafril, Syafrimen; Koderi, Koderi; Patimah, Siti (International Journal of Financial, Accounting, and Management, 2024)
Purpose: This study aims to investigate the management of religious culture in SMP IT Tulang Bawang District, Indonesia. Specifically, it seeks to understand how the school integrates religious values and practices into daily life, fosters tolerance and respect for diverse faiths, and addresses challenges related to religious education. Methodology: A mixed-methods approach was employed, utilizing qualitative interviews with school administrators, teachers, students, and parents, alongside quantitative data analysis of school documents and surveys. Results: The findings reveal that SMP IT Tulang Bawang implements a comprehensive religious culture management system. This includes mandatory daily prayers, religious studies classes, integration of religious values into various subjects, and extracurricular activities promoting interfaith dialogue and understanding. The study also identifies positive outcomes such as increased religious awareness, tolerance, and respectful behavior among students. However, limitations such as limited resources for religious education and potential challenges in addressing sensitive religious topics were also acknowledged. Limitations: The study's generalizability may be limited due to its focus on a single school and context. Furthermore, potential social desirability bias in responses needs to be considered. Contribution: This study provides valuable insights into the successful management of religious culture in Islamic schools, offering valuable lessons for other educational institutions seeking to foster a values-based and inclusive learning environment. It also highlights the importance of continuous improvement and addressing emerging challenges in religious education.